Dates of the O. P. I., dates of Niké - del Pino Perales, Julio (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In the history of contemporary literature in Aragon, the asocciation between two entities, the Niké cafe and the International Poetic Office (O.P.I.), it’s a literary phenomenon that requires an extensive joint study, as a precursor of the most impotant poetic era of Aragon from the 50’s and 60’s. In this work, I’ll try to determine the history of both enterprises and the course of their relation, untill their junction into what today we know as the poetic group of Niké.